2022
DOI: 10.1021/acschemneuro.2c00473
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Evaluation of 18F-Labeled Chalcone Analogue for Detection of α-Synuclein Aggregates in the Brain Using the Mouse Model

Abstract: In the brains of patients with synucleinopathies such as Parkinson’s disease, dementia with Lewy bodies, and multiple system atrophy, α-synuclein (α-syn) aggregates deposit abnormally to induce neurodegeneration, although the mechanism is unclear. Thus, in vivo imaging studies targeting α-syn aggregates have attracted much attention to guide medical intervention against synucleinopathy. In our previous study, a chalcone analogue, [125I]­PHNP-3, functioned as a feasible probe in terms of α-syn binding in vitro;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…The most relevant finding provided by the autoradiography experiment was the ability of both tracers to differentiate between misfolded proteins. Although some scaffolds successfully afforded a moderate αSYN/Aβ selectivity, the complete lack of binding to Aβ plaques has been displayed solely by the 4-nitrophenyl chalcone derivatives developed by Kaide et al However, these compounds displayed insufficient clearance when injected in the healthy brain of ddY mice. , To the best of our knowledge, 2-styrylbenzothiazoles are the only other scaffold exhibiting such selectivity but additionally offer the basis for extensive structural optimization in the perspective of lower lipophilicity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most relevant finding provided by the autoradiography experiment was the ability of both tracers to differentiate between misfolded proteins. Although some scaffolds successfully afforded a moderate αSYN/Aβ selectivity, the complete lack of binding to Aβ plaques has been displayed solely by the 4-nitrophenyl chalcone derivatives developed by Kaide et al However, these compounds displayed insufficient clearance when injected in the healthy brain of ddY mice. , To the best of our knowledge, 2-styrylbenzothiazoles are the only other scaffold exhibiting such selectivity but additionally offer the basis for extensive structural optimization in the perspective of lower lipophilicity.…”
Section: Discussionmentioning
confidence: 99%
“…These factors highlight the import of high selectivity as a key feature of candidate αSYN tracers. An encouraging αSYN/Aβ selectivity was detected for a chalcone-based scaffold recently proposed by Kaide et al, but its pharmacokinetic profile was unsatisfactory. , General criteria for the successful development of an αSYN PET tracer were outlined by the Michael J. Fox Foundation and are more comprehensively discussed by Korat et al, together with the most relevant scaffolds developed so far …”
Section: Introductionmentioning
confidence: 99%
“…13 shows the ligands that selectivity bind to aSyn fibrils. 54,55,[57][58][59][60][61] Fig. 14 fibrils, and a screen of several indanones by Nan et al demonstrated that all had a higher affinity for Ab fibrils (e.g.…”
Section: Ligand Selectivitymentioning
confidence: 99%
“…We compiled a database of 3457 measurements of ligand–amyloid fibril interactions from the scientific literature. 50–385 The requirements to be included in this database were (1) a known chemical structure, (2) a structure that does not contain metals (metalloligands have been thoroughly reviewed elsewhere in the literature 43,386–391 ), (3) a K d or IC 50 measurement, and (4) a fibril target related to Aβ, tau, or αSyn. Nearly half of the database reports on binding to Aβ fibrils formed in vitro , although recent years has seen a shift in focus toward tau and αSyn fibrils formed in vitro (Table 1).…”
Section: Introductionmentioning
confidence: 99%
“…Among them, the benzothiazole derivative (PP-BTA-4) and the benzofuranone derivative (Tg-52) have been reported as α-syn fluorescent probes and could label α-syn aggregates in in vitro histopathological staining. Besides, indolinone derivative (WC58a), benzimidazole derivative (BI-2), and chalcone derivatives (IDP-3, PHNP-3, and FHCL-2) have been found to have good affinities to α-syn aggregates. With a fluorine or iodine atom in their scaffolds, they have been converted to radiotracers and might be applied in nuclear medicine imaging with further development (Figure ).…”
mentioning
confidence: 99%